PENINGKATAN PENGENALAN KOSA KATA BAHASA INGGRIS PADA ANAK MELALUI PERMAINAN KARTU GAMBAR - Huda, Khairul; Purmadi, Ary; Iman, Nurul (Universitas Pendidikan Mandalika, 2017)
The Increasing English Vocabulary Introduction Through Picture Card Games In ChildrenClass B PAUD Nurul Arafah Sembalia Sub-District East Lombok In The academic year2016/2017 can increase with little direction. The purpose of this research is to know theimprovement of vocabulary introduction in child's English through the picture card game inClass B of PAUD Nurul Arafah of Sembalia Sub-district, East Lombok In The academic year2016/2017. The results showed an increase in vocabulary in English through a picture cardgame in children in the class b PAUD nurul arafah sub district with a little direction. Theresearch method used is to use action research class (Action Research) with the subject ofresearch is Class B PAUD Nurul Arafah District Sembalia East Lombok district with thenumber of subjects 19 children. Technique of collecting data with menggiunakan observation,interview, observation and Sheet In English Through Picture Card Game Image Year2016/2017. assessment (field notes). the results of research in the first cycle is 53.49% and inthe second cycle increased by 77.27% it can be concluded that the increase of the I-II cycleincreased on average by 22.12%. %. From result of research that happened Increase ofIntroduction of SenseKeyword: Increasing English Vocabulary Introduction, Picture Card Games